Comparing creative industries in Europe. (October 2016) - Boix, Rafael; Capone, Francesco; De Propris, Lisa; Lazzeretti, Luciana; Sanchez, Daniel
Creative industries are increasingly understood to contribute to localised innovation and dynamism. This paper provides a methodologically consistent comparison of creative industries across France, Great Britain, Italy and Spain. We map spatial agglomerations of creative activities showing evidence of urban concentration, which for Britain and France coincides with the dominance of capital cities, whilst for Spain and Italy, significant concentrations can also be found in secondary cities. The four countries also differ in the specialisation profiles and in the role played by policy makers. A lack of dove-tailing with the European Union smart agenda is argued to be a cause of concern.